The great chain of legitimacy: Justifying transnational democracy - Frank Nullmeier; Tanja Pritzlaff (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2010)
The idea of a 'chain of legitimation' is a central thought in German constitutional theory. However, the conception of a chain of legitimacy does not appear to be sufficient to justify transnational democracy. Starting from this diagnosis, the paper introduces an alternative conception of transnational legitimacy. In this conception, the layer of legitimacy provided by the chain of legitimation is complemented by a layer of legitimacy that is provided by political practices at the micro-level of the political process. Our conception of transnational legitimacy - which is based on a twofold concept of normativity that distinguishes between an explicit and an implicit dimension of normativity - presents a deeper understanding of where to locate the normative forces at play within the political process. The aim of the paper is to show that at the transnational level, democratic legitimacy can only emerge if the long and abstract legitimation chains are normatively backed by political practices that include explicit references to the will of the people as well as integrative, context-sensitive performances that prevent acts of exclusion. – – Die Idee einer ununterbrochenen, auf das Volk zurückführenden Legitimationskette ist ein zentrales Element der deutschen Staats- und Verfassungslehre. Diese Konzeption erscheint im Kontext der Legitimation transnationaler Demokratie jedoch als ungenügend, da man es hier mit sehr langen, abstrakten Konstruktionen von Legitimationsketten zu tun hat. Vor diesem Hintergrund präsentieren wir in dem vorliegenden Arbeitspapier eine alternative Konzeption transnationaler Legitimität, die die Idee der demokratischen Legitimation über Legitimationsketten um eine komplementäre normative Stützungsstruktur ergänzt. Basierend auf einer Unterscheidung zwischen zwei Dimensionen von Normativität - einer expliziten und einer impliziten Dimension - verortet diese Konzeption die Sicherung transnationaler Legitimität auf der Mikroebene des politischen Prozesses, genauer gesagt auf der Ebene politischer Praktiken. Ziel des Arbeitspapiers ist es zu zeigen, dass demokratische Legitimität auf der transnationalen Ebene nur dann entstehen kann, wenn die langen, abstrakten Legitimationsketten durch politische Praktiken normativ unterfüttert werden, die explizite Verweise auf den Willen des Volkes enthalten sowie durch integrative, kontextsensitive Praktiken, die mögliche Formen der Exklusion verhindern.
Keywords: 300